#TITLE_ALTERNATIVE# - ADI NUGRAHA PUTRA (NIM : 10211002), BAYU
Standard Model was one model with good precision in describing elementary particles and their interactions. In the growth of technology and research in the field of elementary particle, there are several observations which cannot be described using Standard Model. One of the most interesting case was the phenomenology of electroweak symmetry breaking (EWSB), which makes electroweak symmetry breaks down into electromagnetic symmetry which then violate the unitary properties in Standard Model. In order to recover its unitary properties, a radiative correction was conducted but it makes the light Higgs mass looks unnatural. Thus we developed minimum composite Higgs model of which the Higgs mass was a composite of Goldstone boson from the symmetry break down SO(5) ! SO(4). From this model calculation, the unitary restoration depends on a new parameter E which describes the behavior of model in Standard Model and Technicolor. In this model we use effective Higgs mass to describe high energy behavior, but for very high energy, Higgs mass still looks unnatural.